HUBUNGAN POLA TIDUR DENGAN KEJADIAN ACNE VULGARIS PADA MAHASISWA SEMESTER V (LIMA) PROGRAM STUDI ILMU KEPERAWATAN FAKULTAS KEDOKTERAN UNIVERSITAS SAM RATULANGI MANADO - Wulandari, Amelia; Kepel, Billy J.; Rompas, Sefty S. (JURNAL KEPERAWATAN, 2015)
Abstract : Acne vulgaris is a skin disease that become problem for adolescents and teenagers. Many risk factors that may affect the incidence of this disease, such as genetic factors, hormonal, stress, microorganisms Propionibacterium acnes, and other environmental factors. Sleep patterns is considered to be one of the cause of acne vulgaris by some of skin beauty blogs and some general community. This research aimed to analyze the relationship between sleep patterns with the incidence of acne vulgaris.This is an analytic research with case control design. This research using simple random sampling technique amounted to 36 respondents were done on the fifth semester students of Nursing Science Medical Faculty University of Sam Ratulangi on December 2014. The data were collected by distributing questionnaires and observations. Data analysis using chi square test, at the 95% significance level (Î± 0.05). From this research was found that 18 (50.0%), of the respondents suffered from acne vulgaris and most of the students had a good sleep pattern as much as 19 respondents (52.8%). The statistical test for sleep patterns and incidence of acne vulgaris shows the p value is 1.000. There is no relationship between sleep patterns with the incidence of acne vulgaris in the fifth semester students of Nursing Science Medical Faculty University of Sam Ratulangi. Suggestions for further research are expected to examine broader risk factors that can cause the incidence of acne vulgaris. Keywords : Sleep patterns, acne vulgaris Abstrak : Acne vulgaris adalah salah satu penyakit kulit yang sering menjadi masalah bagi remaja dan dewasa muda. Banyak faktor resiko yang dapat mempengaruhi timbulnya penyakit ini, seperti faktor genetik, hormonal, stres, mikroorganisme Propionibacterium acnes, dan faktor lingkungan lainnya. Peranan tidur mulai dianggap berpengaruh terhadap timbulnya acne vulgaris oleh beberapa blog kecantikan dan sebagian masyarakat umum. Penelitian ini bertujuan untuk menganalisis hubungan pola tidur dengan kejadian acne vulgaris.Penelitian ini bersifat analitik dengan desain case control. Penelitian menggunakan tehnik simple random sampling berjumlah 36 responden yang dilakukan pada mahasiswa semester lima Program Studi Ilmu Keperawatan Fakultas Kedokteran Universitas Sam Ratulangi Manado pada Desember tahun 2014. Pengumpulan data dilakukan dengan menyebarkan kuesioner dan observasi. Analisis data menggunakan uji chi square, pada tingkat kemaknaan 95% (Î± 0,05). Dari penelitian didapati bahwa 18 orang (50,0%), dari responden menderita acne vulgaris dan sebagian besar mahasiswa memiliki pola tidur yang baik sebanyak 19 responden (52,8%). Uji statistika dari pola tidur dan kejadian acne vulgaris mendapati p-value sebesar 1,000. Tidak ada hubungan signifikan antara pola tidur dengan kejadian acne vulgaris pada mahasiswa semester V (Lima) Program Studi Ilmu Keperawatan Fakultas Kedokteran Universitas Sam Ratulangi Manado. Kata kunci : Pola tidur, acne vulgari